Pengaruh New Product Development,Point Of Purchase Dan Brand Ambassador Terhadap Peningkatan Daya Tarik Konsumen Dalam Pembelian Make Up Make Over Cosmetics (Studi Pada Samudra Supermarket Kediri) - Novi Amanda Wulandari (Politeknik Kampar, 2023)
Current developments in the modern era mean that culinary entrepreneurs must be able to express their own thoughts, creativity and innovation. This research aims to determine the influence of price, location and promotion on purchasing decisions at Jaguar Cafe and Resto Kediri. Researchers chose Jaguar Cafe and Resto Kediri based on existing considerations. This type of research is quantitative research with an associative approach. With a population of 1,703 visitors to the Jaguar Cafe and Resto on Jln. Merak, Karangmulyo Branggahan, Ngadiluwih Kediri District, using non-probability techniques. The samples taken were 94 customers using the Slovin formula. The data analysis technique used is multiple linear regression using SPSS (Statistical Product and Service Solution) software tools. The results of this research show that price has a significant influence on purchasing decisions at Jaguar Cafe and Resto Kediri, Location has an insignificant influence on purchasing decisions at Jaguar Cafe and Resto Kediri, and Promotion has a significant influence on purchasing decisions at Jaguar Cafe and Resto Kediri.